Transformation Theory - Postmodern Issues - Jack Mezirow (Adult Education Research Conference, 1999)
This paper briefly comments on selected issues raised by postmodern writers regarding Transformation Theory, as developed by the author. Issues include situated learning, autonomy, teleology, meta-narratives, reason and the self. A brief summary of Transformation Theory will be available at this presentation.